2023
DOI: 10.22487/27765660.2022.v2.i3.16203
|View full text |Cite
|
Sign up to set email alerts
|

Classifiying The Factors Influencing The Human Development Index in Riau Province using Principal Component Analysis

Abstract: The Human Development Index is a critical indicator of economic growth. Several factors, including average length of schooling (X1), expected length of schooling (X2), life expectancy at birth (X3), number of health workers (X4), number of health facilities (X5), spending per capita (X6), open unemployment rate (X7), number of poor people (X8), percentage of households with proper drinking water sources (X9), and GRDP growth rate (X10), can influence the Human Development Index. The purpose of this research wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…K-medoids can overcome the weakness of k-means which tends to be sensitive to outliers that may deviate from the data distribution (Wicaksono & Yolanda, 2021). Furthermore, research on Human Development Index (HDI) in Riau Province classifying the factors that influence HDI in Riau Province in 2021 was discussed by Erda et al, (2023). It was found that there were three categories, namely service quality, health facilities and economic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…K-medoids can overcome the weakness of k-means which tends to be sensitive to outliers that may deviate from the data distribution (Wicaksono & Yolanda, 2021). Furthermore, research on Human Development Index (HDI) in Riau Province classifying the factors that influence HDI in Riau Province in 2021 was discussed by Erda et al, (2023). It was found that there were three categories, namely service quality, health facilities and economic conditions.…”
Section: Introductionmentioning
confidence: 99%